As estratégias utilizadas no desenvolvimento do PDI em duas universidades federais da região sul - Guedes, Eleanara Pereira (2013)
The aim was to investigate the strategies adopted for the preparation of the Institutional Development Plan (IDP) at the Federal University of Santa Maria (UFSM) and the Federal University of Paraná (UFPR). To conduct this study used a qualitative approach through a case study. The research was descriptive, so that the insights presented the planning team and UFSM UFPR regarding strategies for the preparation of the IDP. With regard to the object of the study was to research and internal documents UFSM UFPR. The subjects of this study were the Deans and Technical-administrative planning team who work or worked in the IDP of the institutions under study were applied in the research tool compounds with nineteen open questions. The research was through the internet. This study investigates the process of PDI in UFSM UFPR and analysis in the following categories: preparation, implementation, monitoring and evaluation, and difficulties. The strategies adopted in the IDP (2011-2015) / UFSM showed that the institution is concerned with the management of knowledge, collective decisions, with the widest possible participation of the university community in the IDP process. Strategies PDI (2012-2016) / UFPR were deliberated by the Central Administration, which determined the modules, themes and units responsible, showing formal characteristics in the process, the strategies were flexible, participatory, and dynamic. The 2nd category analysis of the IDP implementation, monitoring and evaluation can be concluded that the two institutions experiencing different moments of this phase. The main barriers identified in implementing the IDP / (2011-2015) / UFSM were the lack of a monitoring system of actions, lack of knowledge of the actions contained in the IDP and the lack of culture of planning. UFPR in the process of IDPs (2012-2016) is to have recent reviews. The research found that the process of sensitization in IFESs PDI should preferably be initiated early in the process, because the main factor to be discredited PDI and lack of knowledge of the importance of it, so that should be performed an intense raising the university community.